(a-.5y)(a+.5y)=

Simple and best practice solution for (a-.5y)(a+.5y)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (a-.5y)(a+.5y)= equation:


Simplifying
(a + -0.5y)(a + 0.5y) = 0

Multiply (a + -0.5y) * (a + 0.5y)
(a(a + 0.5y) + -0.5y * (a + 0.5y)) = 0
((a * a + 0.5y * a) + -0.5y * (a + 0.5y)) = 0

Reorder the terms:
((0.5ay + a2) + -0.5y * (a + 0.5y)) = 0
((0.5ay + a2) + -0.5y * (a + 0.5y)) = 0
(0.5ay + a2 + (a * -0.5y + 0.5y * -0.5y)) = 0
(0.5ay + a2 + (-0.5ay + -0.25y2)) = 0

Reorder the terms:
(0.5ay + -0.5ay + a2 + -0.25y2) = 0

Combine like terms: 0.5ay + -0.5ay = 0.0
(0.0 + a2 + -0.25y2) = 0
(a2 + -0.25y2) = 0

Solving
a2 + -0.25y2 = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '0.25y2' to each side of the equation.
a2 + -0.25y2 + 0.25y2 = 0 + 0.25y2

Combine like terms: -0.25y2 + 0.25y2 = 0.00
a2 + 0.00 = 0 + 0.25y2
a2 = 0 + 0.25y2
Remove the zero:
a2 = 0.25y2

Simplifying
a2 = 0.25y2

Take the square root of each side:
a = {-0.5y, 0.5y}

See similar equations:

| (4x+5y)(4x-5y)= | | 8x^3(2x^2-6x+9)= | | Ln(y)=4lnx+3 | | Lny=4lnx+3 | | -29-(-5)= | | (1.25a^2-2)(1.25a^2+2)= | | -6=(2/w) | | y=2.37874x+0.005025 | | 1+(4)+5+(8)= | | 56+(-21)= | | 31/2V | | 2x-201/13 | | (5x-0.2)(5x+0.2)= | | (9x-.5)(9x+.5)= | | p=5y+3x | | 6(y-3)(2y-1)= | | 5-2v= | | 8x+4y=116 | | 6-(-2)-(-5)= | | x+r=s | | (2x-9)(x+5)= | | (2/5)m=-32 | | 3y/10=y-1/6 | | P=2(2.5+5) | | (2/3)m=-96 | | P=2(10+5) | | 15=2(a+b) | | 4/5=x/6 | | ym=n | | X/-3=1 | | -6=3/4n | | 4x-(3x+6)=5x-30 |

Equations solver categories